2022
DOI: 10.4314/ijbcs.v16i4.17
|View full text |Cite
|
Sign up to set email alerts
|

Practices and damages encountered by wholesale traders during 'Kponan' yams (Dioscorea cayenensis-rotundata) storage in Abidjan, Côte d'Ivoire

Abstract: Yam wholesalers who practice speculative storage sometimes suffer significant losses the level of which has been little studied. Thus, this work was carried out to study the practices and deterioration factors of 'Kponan' yam during storage. To achieve this, 51 yam wholesalers in 4 communes of Abidjan (Abobo, Adjamé, Yopougon and Treichville) were interviewed using a survey form. The data showed that according to storage practices, yams are preferentially grouped by variety (100%) and old yams separately (88.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…After the 3 months of field storage, rot (22.86% -60.00%) was the most significant injury recorded. These results corroborate those of several authors [16] [23], who identified rot and weight loss as the main damages recorded when "Kponan" was kept under the influence of heat. Losses attributed to more than 30% to 50% during field storage were attributable to insects, rats and chemicals [23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…After the 3 months of field storage, rot (22.86% -60.00%) was the most significant injury recorded. These results corroborate those of several authors [16] [23], who identified rot and weight loss as the main damages recorded when "Kponan" was kept under the influence of heat. Losses attributed to more than 30% to 50% during field storage were attributable to insects, rats and chemicals [23].…”
Section: Discussionsupporting
confidence: 92%
“…Other factors such as heat, mold, animals (rodents and insects), germination, field storage conditions and chemicals use [23], coupled with soil quality and fallow time [16], may also reduce the storage time of "Kponan" yam. According to these authors, the combination of cultivation methods, conservation methods, soil poverty and short fallow time are the factors implicated in reducing the life span of "Kponan" yam in conservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Unfortunately, the Kponan variety, which is the most prized of this complex by consumers, [14][15][16] is the most prone to rot during conservation and storage. 16 Kponan yams sold on Abidjan wholesale markets comes from six geographical origins, the main ones being Bondoukou (60%), Bouna (33.3%) and Kouassi-Kouassikro (6.7%). 15 Despite the importance of yams in Côte d'Ivoire's food system, annual production is still insufficient to meet food needs, due to tuber storage, which causes weight losses ranging from 65% to 85% 17 and losses of up to 50% of the harvest caused by dehydration, harvest wounds, pests, rats and the use of chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…15 Despite the importance of yams in Côte d'Ivoire's food system, annual production is still insufficient to meet food needs, due to tuber storage, which causes weight losses ranging from 65% to 85% 17 and losses of up to 50% of the harvest caused by dehydration, harvest wounds, pests, rats and the use of chemicals. 13,15,16,18 As a result, these losses greatly reduce yields and, consequently, the quantity of tuber seeds, sometimes leading to the disappearance of certain varieties. According to several authors, 11,19 growing, harvesting and storing techniques of Kponan yam in the field have an impact on its shelf life.…”
Section: Introductionmentioning
confidence: 99%